SOEP-IS 2016 - INNO: Variables from the innovation modules - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The File INNO contains individual data from the innovative modules with one row per respondent and wave.
Keywords: 330